Surgical interventions in abdominal tuberculosis: a clinico-pathological study - Jain, Sanjay; Gaur, Shivam; Songra, M. C. (International Surgery Journal, 2017)
Background: Abdominal tuberculosis is a common site for extrapulmonary TB, which affects young population and poses a big diagnostic and therapeutic challenge. Methods: A total 100 cases suspicious of abdominal tuberculosis undergoing surgical interventions were studied in the present study in our institute for period of 18 Months. Results: Males belonging to young age group of 21-40 were most commonly affected. Primary abdominal tuberculosis was the most common etiopathological cause. Abdominal pain seen in 86% of patients. Abdominal tenderness seen in 84% of patients. The condition was more common in people of low socioeconomic status. Primary abdominal tuberculosis was more common than cases secondary to pulmonary TB. Majority of patients had abdominal pain and distention at the time of presentation. Bowel adhesions was the most common intra operative finding followed by stricture, mesenteric lymphadenopathy and bowel perforations. Majority of biopsies show granulomatous lesions. Exploratory laprotomy with adhesiolysis was the most common single procedure performed multiple procedures with covering ileostomy resulted in better survival, lower serious post-operative complication rate and shorter duration of hospital stay. Conclusions: Young males are most commonly affected usually presents with abdominal pain. Bowel adhesions and strictures were most common intraoperative finding, an ileostomy in selected cases found to be result in significant reduction in morbidity and mortality in cases of abdominal tuberculosis undergoing surgery.